TINJAUAN YURIDIS AKIBAT PERUBAHAN PERUNTUKKAN TANAH PERTANIAN KE NON PERTANIAN SEBAGAI DASAR PENETAPAN PBB DAN BPHTB - ROSERIA NATALIA GULTOM (Ilmu Hukum Prima (IHP), 2021)
The increase in land transfer and use, such as farm land becomes non farm (housing and industry), rural land becomes urban land which makes its price higher. The increase in the land price (from farm land to urban land) is caused by two factors: there are the land transfer from farm land to non-farm land and business roperty. The increase in land price influences NJOP (taxable item market value) as the basis for the assessment of PBB (Tax on Land and Building). The objective of the research was to find out and to analyze the legal consequence of the transfer of the use of land from farm land to non-farm land, to find out and to analyze the impact of the use of land on NJOP, and to find out the basis for imposing PBB. The results of the research shows thats it is very common that he person who transfers the land from farm land to non- farm land does not follow the procedure so that it is illegal. Therefore, the regulation is needed to protect irrigated rice fields and the impact of the change in the land use by the increase of the price of the farm land to the non-farm land which eventually increase NJOP and influences the PBB. The imposition of PBB and BPHTB is based on SISMIOP in which its operation is referred to the data and the assessment by optimizing the storing, processing, presenting, distributing, and analyzing information about PBB.